Factors Influencing Career Choices Among Final Year Students in Universiti Tun Hussein Onn Malaysia - Najwa Hanim Mohamad Zakahar,; Ahmad, Nurazwa; Fadillah Ismail, (Research in Management of Technology and Business, 2024)
Given the unemployment issue, it is understandable that final-year students are often concerned about their career prospects. They are likely contemplating what their future holds after university and the factors that will influence their career decisions. This study is conducted to identify the factors that influence career choices among final year students in UTHM. The main objective of this study is to identify the level of family influence, personal interest, peer influence, gender factors and salary factors among final year students in UTHM and to investigate the dominant factors. This study is using a descriptive method in achieving the research objective. In addition, the data collected was processed using Statistical Package for Social Science (SPSS). The number of respondents participating in the survey was 211 representing 52.75% response rate. Data analysis shows that the dominant factor of this study is personal interest factor, followed by salary factor, peer influence, gender factor, and lastly family influence. The highest mean score is 3.966 while the lowest mean score is 3.340. The results show that final year students in UTHM prioritize their own interests and suitability when making career decisions along with salary factor. The findings of this study have important implications for career counseling and educational interventions, suggesting that a focus on aligning personal interests and financial expectations with career choices can enhance student outcomes.